2019
DOI: 10.1039/c9cp02307k
|View full text |Cite
|
Sign up to set email alerts
|

In-gap state generated by La-on-Sr substitutional defects within the bulk of SrTiO3

Abstract: Free energy perturbation (FEP) approaches with stratification see widespread and increasing use in computational studies of biologically relevant molecules. However, when the molecular system are characterized by a complex conformational free energy landscape, the assessment of convergence remains a concern for many practitioners. The sampling problem in FEP has been authoritatively addressed in a recent perspective paper [ D. Mobley, J. Comput. Aided Mol. Des., 26, 93 2012 ], incisively entitled "Let's get ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…According to previous experimental and theoretical studies, lattice defects and distortions are considered the origin of the near-VB defect states of oxides. [26][27][28][29][30] Since surface and/or bulk electronic states of oxides are strongly correlated with the interfacial structure, [31][32][33][34] we prepared two types of SnO TFTs on (001)-oriented yttria-stabilized zirconia (YSZ) singlecrystal substrates with different surface morphologies. We observed that the optimum growth temperature of SnO films was different depending on the surface conditions of YSZ substrates; further, the operation mode changed between the ambipolar and the p-channel for SnO-TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous experimental and theoretical studies, lattice defects and distortions are considered the origin of the near-VB defect states of oxides. [26][27][28][29][30] Since surface and/or bulk electronic states of oxides are strongly correlated with the interfacial structure, [31][32][33][34] we prepared two types of SnO TFTs on (001)-oriented yttria-stabilized zirconia (YSZ) singlecrystal substrates with different surface morphologies. We observed that the optimum growth temperature of SnO films was different depending on the surface conditions of YSZ substrates; further, the operation mode changed between the ambipolar and the p-channel for SnO-TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the resulting properties can be quite sensitive to the specific type of doping. [12][13][14][15][16][17][18][19][20][21][22] Regarding oxygen-vacancy doping in SrTiO 3 , perhaps the most pressing open question is the nature of the introduced charge, with different experimental measurements leading to apparently contradictory conclusions. On one hand, it is known that even very low concentrations of oxygen vacancies cause metallicity, with transport measurements indicating an increase in carrier density with increasing oxygen vacancy concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Angle-resolved photoemission spectroscopy (ARPES) is a powerful and unique technique for investigating the electronic structure of materials experimentally based on the well-known relationship between the kinetic energy and emission angle of photoelectron. 21,22 Owing to its surface sensitivity, a clean and well-defined surface is indispensable for observing these intrinsic electronic structures of materials. Sputtering and/or annealing processes have conventionally been applied to prepare such surfaces.…”
mentioning
confidence: 99%
“…The uppermost valence band is clearly observed for LH polarization but not for LV polarization. On the basis of dipole transition selection rules for optical transitions, 21,22 the photoelectrons are only detected when the initial state is symmetric and antisymmetric, with respect to the symmetry operation, to the detection (mirror) plane for LH and LV polarizations, respectively. Because the point group along the symmetric Γ−X (Γ−Μ) line is C 2v , the bands with Γ 1 and Γ 2 (Γ 1 and Γ 4 ) symmetries should be observed for LH polarization, whereas the bands with Γ 3 and Γ 4 (Γ 2 and Γ 3 ) symmetries should be observed for LV polarization.…”
mentioning
confidence: 99%
See 1 more Smart Citation